Dissociative adsorption of molecular hydrogen on BN-doped graphene-supported aluminum clusters - Kumar, Deepak; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2017)
The present work demonstrates dissociative adsorption of molecular hydrogen on supported and unsupported aluminum Wclusters (Al-n, n = 4-8, 13) using density functional theory based calculations. The studies reveal that the presence of a BN-doped graphene surface support reduces the dissociative adsorption barrier of the bond in molecular hydrogen on even atom clusters. In particular, supported Al-6 demonstrates a barrier-less dissociative adsorption toward the H-2 molecule. These results demonstrate the excellent potential of supported Al nanoparticles for hydrogen storage and also the potential of doped graphene systems are catalyzing supports.